2020
DOI: 10.1016/j.redox.2020.101704
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of hydrogen sulfide in diabetes-impaired angiogenesis and ischemic tissue repair

Abstract: Diabetes is one of the most prevalent metabolic disorders and is estimated to affect 400 million of 4.4% of population worldwide in the next 20 year. In diabetes, risk to develop vascular diseases is two-to four-fold increased. Ischemic tissue injury, such as refractory wounds and critical ischemic limb (CLI) are major ischemic vascular complications in diabetic patients where oxygen supplement is insufficient due to impaired angiogenesis/neovascularization. In spite of intensive studies, the underlying mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 168 publications
(281 reference statements)
1
35
0
Order By: Relevance
“…Studies have suggested that the cardioprotective effects of H 2 S are mediated through various pathways 71 , 92 94 . H 2 S has an important role in promoting angiogenesis and ameliorating type 2 diabetes mellitus that also protect against IRI 8 , 95 , 96 . Endogenous H 2 S production also augments antioxidant signalling via nuclear factor erythroid 2-related factor 2, reduces nuclear factor-κB (NF-κB)-mediated inflammatory signalling and facilitates NO signalling 60 , 97 .…”
Section: Sulfides In the Cardiovascular Systemmentioning
confidence: 99%
“…Studies have suggested that the cardioprotective effects of H 2 S are mediated through various pathways 71 , 92 94 . H 2 S has an important role in promoting angiogenesis and ameliorating type 2 diabetes mellitus that also protect against IRI 8 , 95 , 96 . Endogenous H 2 S production also augments antioxidant signalling via nuclear factor erythroid 2-related factor 2, reduces nuclear factor-κB (NF-κB)-mediated inflammatory signalling and facilitates NO signalling 60 , 97 .…”
Section: Sulfides In the Cardiovascular Systemmentioning
confidence: 99%
“…The brain, liver, kidney, and other organs produce H 2 S [ 7 ]. The cellular biogenesis of H 2 S is based on the desulfuration of cysteine or homocysteine, a process involving mainly three enzymes: cystathionin-β-synthase (CBS), cystathionin-γ-lyase (CSE), and 3-mercaptopyruvate sulfurtransferase (MST) [ 61 ]. H 2 S biogenesis at the mitochondria level implies cysteine aminotransferase (CAT) that catalyzes L-cysteine and glutamate to 3-mercaptopyruvate and α-ketoglutarate.…”
Section: Resultsmentioning
confidence: 99%
“…The relation between diabetes-induced endothelial dysfunction and H 2 S impairment is now well established (for review see [ 77 , 97 ]). H 2 S levels have been observed to be reduced in rats with diabetes induced by streptozotocin (STZ) and in subjects with type 2 diabetes mellitus [ 98 , 99 , 100 , 101 , 102 ].…”
Section: Cardiovascular Diseases Associated With Altered Levels Ofmentioning
confidence: 99%